2000
DOI: 10.1006/pmpp.2000.0291
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacteria-mediated induced systemic resistance (ISR) in Arabidopsis requires sensitivity to jasmonate and ethylene but is not accompanied by an increase in their production

Abstract: Plants develop an enhanced defensive capacity against a broad spectrum of plant pathogens after colonization of the roots by selected strains of nonpathogenic biocontrol bacteria. In Arabidopsis thaliana, this induced systemic resistance (ISR) functions independently of salicylic acid but requires an intact response to the plant hormones jasmonic acid (JA) and ethylene. To further investigate the roles of JA and ethylene in the ISR signalling pathway, the levels of these signalling molecules were determined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
121
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(133 citation statements)
references
References 60 publications
9
121
1
2
Order By: Relevance
“…Analysis of local and systemic levels of jasmonic acid and ethylene revealed that ISR is not associated with changes in the production of these signal molecules [48]. This suggests that the induced resistance is based on an enhanced sensitivity to these plant hormones rather than on an increase in their production.…”
Section: Priming During Isr In Arabidopsismentioning
confidence: 97%
See 2 more Smart Citations
“…Analysis of local and systemic levels of jasmonic acid and ethylene revealed that ISR is not associated with changes in the production of these signal molecules [48]. This suggests that the induced resistance is based on an enhanced sensitivity to these plant hormones rather than on an increase in their production.…”
Section: Priming During Isr In Arabidopsismentioning
confidence: 97%
“…Although ethylene plays an important role in the ISR signalling pathway of Arabidopsis, ethylene production is not increased in ISRexpressing tissue [52]. However, after treatment with a saturating 1 mM dose of the ethylene precursor 1-aminocyclopropane-1-carboxylate (ACC), ISR-expressing plants emit significantly more ethylene than ACC-treated control plants [48,52]. Evidently, the capacity to convert ACC to ethylene is increased in ISR-expressing plants.…”
Section: Priming During Isr In Arabidopsismentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas SAR is associated with local and systemic accumulation of SA and the expression of pathogenesis-related (PR) genes (Métraux et al 1990;Uknes et al 1992;Sticher et al 1997;Mauch-Mani and Métraux 1998;Durrant and Dong 2004), ISR requires responsiveness of the plant to JA and ET (Pieterse et al 1996(Pieterse et al , 1998. However, ISR is not associated with an increased synthesis of these hormones, nor with an increased expression of known defense-related genes (Van Wees et al 1999;Pieterse et al 2000;Verhagen et al 2004).…”
Section: Activation Of Plant Inducible Defense Responsesmentioning
confidence: 99%
“…This suggests that the resistance attained was not associated with major increases in the levels of either JA or ethylene. Indeed, analysis of JA levels in, and ethylene production by, leaves treated with WCS417r and untreated plant parts expressing ISR, revealed no changes in the production of these signal molecules [20]. Therefore, it is assumed that the JA and ethylene dependency of ISR is based on enhanced sensitivity to these hormones, rather than on an increase in their production.…”
Section: Introductionmentioning
confidence: 98%